2017
DOI: 10.5194/esd-8-577-2017
|View full text |Cite
|
Sign up to set email alerts
|

Young people's burden: requirement of negative CO<sub>2</sub> emissions

Abstract: Abstract. Global temperature is a fundamental climate metric highly correlated with sea level, which implies that keeping shorelines near their present location requires keeping global temperature within or close to its preindustrial Holocene range. However, global temperature excluding short-term variability now exceeds +1 • C relative to the 1880-1920 mean and annual 2016 global temperature was almost +1.3 • C. We show that global temperature has risen well out of the Holocene range and Earth is now as warm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
196
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(200 citation statements)
references
References 201 publications
(280 reference statements)
3
196
0
1
Order By: Relevance
“…Such contrasting ice-mass distributions between successive glacial maxima highlight significant complexity in the processes that drive glaciation into different 'modes' (e.g., Liakka et al, 2016). The difference also has repercussions for glacioisostatic adjustment (GIA) studies of sea-level history during the LIG, which was about 1 C warmer than the Holocene (Clark and Huybers, 2009;Turney and Jones, 2010;McKay et al, 2011;Hoffman et al, 2017;Hansen et al, 2017), with sea levels that reached 4e10 m higher than today Dutton and Lambeck, 2012;Grant et al, 2012;Stocker et al, 2013;Dutton et al, 2015aDutton et al, , 2015b. Dendy et al (2017) investigated the sensitivity of the predictions of the last interglacial highstand to uncertainties in the configuration of the major northern hemisphere ice sheets during MIS 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such contrasting ice-mass distributions between successive glacial maxima highlight significant complexity in the processes that drive glaciation into different 'modes' (e.g., Liakka et al, 2016). The difference also has repercussions for glacioisostatic adjustment (GIA) studies of sea-level history during the LIG, which was about 1 C warmer than the Holocene (Clark and Huybers, 2009;Turney and Jones, 2010;McKay et al, 2011;Hoffman et al, 2017;Hansen et al, 2017), with sea levels that reached 4e10 m higher than today Dutton and Lambeck, 2012;Grant et al, 2012;Stocker et al, 2013;Dutton et al, 2015aDutton et al, , 2015b. Dendy et al (2017) investigated the sensitivity of the predictions of the last interglacial highstand to uncertainties in the configuration of the major northern hemisphere ice sheets during MIS 6.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the size and spatial distribution of land ice during past glacials determines crustal rebound processes when ice masses melt, which in turn affects sea-level reconstructions for subsequent interglacials. The latter are key to investigations of sea-level changes above the present level during warmer-than-present interglacials (e.g., the Last Interglacial, LIG,~130-118 kyr ago (ka); Hibbert et al, 2016;Hoffman et al, 2017;Hansen et al, 2017), which can reveal ice-sheet disintegration processes of relevance to the future (e.g., Dutton and Lambeck, 2012;Dutton et al, 2015a,b;Yamane et al, 2015;DeConto and Pollard, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The laws of nature allow humanity not to overspend this budget, but the required replacement of fossil fuels by renewables and both curves, the total CO 2 put into the atmosphere is 525 GtC, a number chosen because it happens to reproduce the rates of emission reduction contained in the Hansen et al paper, i.e. 3.5% in 2003Hansen et al , 6% in 2013Hansen et al , and 15% in 2020 As an important aside, beyond the scope of the this paper, is that Hansen et al have concluded, in view the industrialized 5 world's lack of action, that the climate can only be stabilized by "negative emissions," i.e., by extraction of CO 2 from the air (Hansen et al, 2017). This approach will be very expensive; it is also fraught with danger because of the difficulty of accurately predicting the instabilities associated with our human time scale irreversible disintegration of ice sheets and ice shelves Hansen (2005).…”
mentioning
confidence: 94%
“…• C global mean temperature increase is a "guardrail" that protects life on Earth from the 15 essentially irreversible harm of run-away climate change (Geden, 2015;Friedman, 2015;Knutti et al, 2016) Hansen et al in (Hansen et al, 2008Hansen et al, 2017). This paper presented a simple model to keep track of how much of the global greenhouse gas budget is spent in carbon-equivalent units, a choice that is 5 consistent with the precautionary principle.…”
mentioning
confidence: 99%
See 1 more Smart Citation